Meningkatkan Hasil Belajar Tematik Kelas III Menggunakan Model Pembelajaran PBL dengan Berbantuan media PPT - Sejati, Nanda Mutiara (Paedagogie, 2023)
This study aims to improve student learning outcomes by applying the Problem Based Learning (PBL) learning model using Power Point (PPT) media. The subjects of this study were 26 students in grade III of the 2022 school year. Learning outcome data are obtained from evaluation tests, learning outcome data are analyzed by quantitative descriptive methods, and obstacles encountered in research are analyzed by qualitative descriptive methods. The results of the research that have been carried out obtained data that in the pre-cycle completeness of student learning outcomes 42.30% with an average score of 68.61. Furthermore, in cycle I the percentage of completeness of learning outcomes was 69.24% with an average score of 77.11%, in cycle II the percentage of completeness of student learning outcomes was 88.47%. It can be concluded that the application of the PBL learning model can improve the thematic learning outcomes of grade III students with the help of PPT media can increase students' active participation in the learning process.